Understanding the Role of Metakaolin towards Mitigating the Shrinkage Behavior of Alkali-Activated Slag - Bo Fu (MDPI AG, 2021)
This research investigates the mechanism of metakaolin for mitigating the autogenous and drying shrinkages of alkali-activated slag with regard to the activator parameters, including concentration and modulus. The results indicate that the incorporation of metakaolin can decrease the initial viscosity and setting time. Increasing activator concentration can promote the reaction process and shorten the setting time. An increase in the metakaolin content induces a decrease in compressive strength due to reduced formation of reaction products. However, increasing activator dosage and modulus can improve the compressive strength of alkali-activated slag containing 30% metakaolin. The inclusion of metakaolin can mitigate the autogenous and drying shrinkage of alkali-activated slag by coarsening the pore structure. On the other hand, increases in activator concentration and modulus result in an increase in magnitude of the autogenous and drying shrinkage of alkali-activated slag containing metakaolin. The influence of the activator modulus on the shrinkage behavior of alkali-activated slag-metakaolin binary system should be further investigated.